2019
DOI: 10.1177/0954407019862079
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intelligent proportional-integral-like fuzzy knowledge–based controller using chaos-enhanced accelerated particle swarm optimization algorithm for transient calibration of air–fuel ratio control system

Abstract: The self-adaptive and highly robust proportional-integral-like fuzzy knowledge–based controller has been developed to regulate air–fuel ratio for gasoline direct injection engines, in order to improve the transient response behaviour and reduce the effort to be spent on calibration of parameter settings. However, even though the proportional-integral-like fuzzy knowledge–based controller can automatically correct the initially calibrated proportional and integral parameters, a more appropriate selection of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The proposed approach follows the idea of critical knowledge for retaining the consistence of troubleshooting patterns. 4346 Meanwhile, the essential and adequate knowledge are also mentioned in critical knowledge to the operations of a firm. 47,48 Knowledge is composed of criteria and contextualized parameters that are crucial for the collaborative troubleshooting service.…”
Section: Patterns Of Knowledge Configurationmentioning
confidence: 99%
“…The proposed approach follows the idea of critical knowledge for retaining the consistence of troubleshooting patterns. 4346 Meanwhile, the essential and adequate knowledge are also mentioned in critical knowledge to the operations of a firm. 47,48 Knowledge is composed of criteria and contextualized parameters that are crucial for the collaborative troubleshooting service.…”
Section: Patterns Of Knowledge Configurationmentioning
confidence: 99%
“…Simulation results demonstrated that the proposed robust H ∞ controller based on genetic algorithm offers superior low-frequency disturbance rejection, high-frequency noise rejection, and overall performance. The study in [ 11 ] introduced an enhanced intelligent PI-like fuzzy knowledge-based controller for regulating the AFR in gasoline direct injection engines. The controller utilized a chaos-enhanced accelerated particle swarm optimization algorithm to automatically determine parameters, improving transient performance.…”
Section: Introductionmentioning
confidence: 99%
“…For Level I, AI models are used to model the nonlinearity of the vehicle systems, e.g., engine performances [15]. The AI models are expected to assist in some R&D tasks, e.g., component sizing [16] and control calibration [17] if they have the capability of offline optima searching (Level II). By incorporating AI-based modelling and AI-based optimization, the Level III AI models can deal with model predictive control tasks that allow the vehicle system to be optimized online [18,19].…”
Section: Introductionmentioning
confidence: 99%